Seizure Characteristics and Background Amplitude-Integrated Electroencephalography Activity in Neonatal Rats Subjected to Hypoxia–Ischemia - Sun, Xiaowei; Xue, Fenqin; Wen, Jialin; Gao, Limin; Li, Yang; Jiang, Qianqian; Yang, Lijun; Cui, Hong (Frontiers in Pediatrics, 2022)
Objective Perinatal hypoxic–ischemic encephalopathy (HIE) is a major cause of epilepsy and chronic neurologic morbidity in premature infants. This study aimed to investigate the characteristics of acute seizures and the pattern of background activity on amplitude-integrated electroencephalography (aEEG) in neonatal rats with HIE. Methods Hypoxia–ischemia (HI) was induced in postnatal day (P) 3 neonatal rats (n = 12) by ligation of the left carotid artery and exposure to airtight hypoxia for 2 h. Data regarding seizure type, frequency, and duration and those related to neurobehavioral development were collected, and the integrated power of background EEG was analyzed to evaluate the effect of HI. Results All neonatal rats in the HI group experienced frequent seizures during hypoxia, and 83.3% of rats (10/12) experienced seizures immediately after hypoxia. Seizure frequency and duration gradually decreased with increasing age. The mortality rate of the HI group was 8.33% (1/12); 120 h after HI induction, only 27.3% (3/11) of pups had low-frequency and short-duration electrographic seizures, respectively. HI rats, which presented seizure activities 96 h after HI insult, exhibited an increase in righting reflex time and a decrease in forelimb grip reflex time. Background EEG was significantly inhibited during HI induction and immediately after hypoxia and gradually recovered 72 h after hypoxia. Conclusion Seizures caused by HI brain damage in premature infants can be simulated in the P3 neonatal rat model.